Reusability of Photocatalytic CoFe2 O4@ZnO Core–Shell Nanoparticles for Dye Degradation - Suharyadi, Edi (ECS Journal of Solid State Science and Technology, 2022)
The reusability of CoFe2 O 4 @ZnO core–shell nanoparticles (NPs) for the photocatalytic degradation of methylene blue (MB) under UV radiation was successfully investigated. CoFe 2 O 4 @ZnO NPs with various CoFe2 O 4–to–ZnO concentration ratios were synthesized as magnetic photocatalysts. The X-ray diffraction spectra showed that the NPs had a cubic spinel ferrite phase structure and a hexagonal wurtzite phase of ZnO. Fourier-transform infrared spectra showed the presence of Moct -O, Mtet -O, and Zn–O at 593, 347–389, and 410–429 cm−1 , respectively. The CoFe 2 O 4 @ZnO NPs had a saturation magnetization of approximately 30 emu g−1 and a coercivity of approximately 280 Oe. The absorbance spectra showed that the absorbance peak of the CoFe 2 O 4 @ZnO NPs broadened and shifted to the right (higher wavelength) with increasing ZnO concentration. The CoFe 2 O 4 @ZnO NPs with higher ZnO concentrations exhibited higher photocatalytic activities and degradation rates. The enhancement of MB degradation can be attributed to the formation of an internal structure between CoFe 2 O 4 and ZnO. The degradation rate of CoFe2 O 4 @ZnO decreased slightly after each successive recycle. The results indicated that the recycled CoFe2 O 4 @ZnO NPs could be reused three times for photocatalytic degradation. As there is no significant decrease in the photocatalytic degradation after four successive recycles, the CoFe 2O 4 @ZnO NPs are suitable for application in dye degradation. © 2022 The Author(s). Published on behalf of The Electrochemical Society by IOP Publishing Limited. This is an open access article distributed under the terms of the Creative Commons Attribution 4.0 License (CC BY, http://creativecommons.org/licenses/ by/4.0/), which permits unrestricted reuse of the work in any medium, provided the original work is properly cited